Determinants of High-Growth Enterprises in Poland - Teresa Kraśnicka; Wojciech Głód (Problemy Zarządzania, 2016)
The paper explains the concept and significance of high-growth enterprises and discusses selected factors that may have an impact on high growth dynamics. It is against such a background that the results of almost 4,000 Polish companies considered to be in the high-growth category are presented. This includes profiles of selected company qualities taking into account their size, location, core activity, and capital. The decided bulk from among the examined companies (almost 83%) consists of small and medium enterprises, where their locations in the individual regions of Poland does not significantly depart from basic entrepreneurial indicators by territory. The research made it possible to answer a question relating to ties among selected factors that can influence the dynamic growth of companies (employment level and capital value), where the measure of high-growth is expressed as revenue over time. No correlation was found between these variables, but thanks to the application of nonparametric analysis of variance, statistically significant differences between the levels of the sales growth coefficient in particular enterprise categories was revealed (by employment, core activity, and capital).